2019
DOI: 10.3390/polym11091396
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Solubility, Stability, and Herbicidal Activity of the Herbicide Diuron by Complex Formation with β-Cyclodextrin

Abstract: The herbicide diuron is hardly soluble in water and most organic solvents and is usually made into a wettable powder or mixed with soil when used, which causes environmental risk and a reduction in herbicidal efficacy. In this study, the physicochemical properties were changed by using β-cyclodextrin (β-CD) to encapsulate diuron to form an inclusion complex. Some key technologies, including X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 39 publications
3
19
0
1
Order By: Relevance
“…Therefore, the adsorption of PP was mainly attributed to the formation of host-guest inclusion complex between β-CD and PP molecules, and one PP molecule occupied one β-CD molecule. However, the Freundlich adsorption model is also highly fitted, the result may be induced by the non-uniform distribution and interaction of β-CD on the membranes, which demonstrated that the adsorption process was dominated by monolayer adsorption, and multi-molecular layer adsorption coexisted [35,36,37]. In addition, the value of 1/n calculated by the Freundlich model was close to 0.5, which manifested that the β-CD/CS porous membranes had strong adsorption capacity for PP.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the adsorption of PP was mainly attributed to the formation of host-guest inclusion complex between β-CD and PP molecules, and one PP molecule occupied one β-CD molecule. However, the Freundlich adsorption model is also highly fitted, the result may be induced by the non-uniform distribution and interaction of β-CD on the membranes, which demonstrated that the adsorption process was dominated by monolayer adsorption, and multi-molecular layer adsorption coexisted [35,36,37]. In addition, the value of 1/n calculated by the Freundlich model was close to 0.5, which manifested that the β-CD/CS porous membranes had strong adsorption capacity for PP.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, hydrophobic drugs can entirely or partially enter within these lipophilic cavities, and a CD-drug complex is formed by host–guest non-covalent bindings. Hence, CDs potentially can improve the problem with the solubility of hydrophobic poorly soluble drugs in aqueous media through encapsulation of such guest compounds into their cavities when they can match with cavities in terms of polarity, size, shape and properties [ 126 , 129 ]. Formation of a stable supermolecular complex between CDs and larger guest structures is also possible through their hydrophobic groups, which can bind into these CDs cavities [ 126 , 129 ].…”
Section: Magnetic Molecularly Imprinted Polymer (Mmip) Preparationmentioning
confidence: 99%
“…Hydroxypropyl-β-cyclodextrin (HPβCD) is widely used as a solubilizing agent and carrier with rapid dissolution for much poorly water-soluble ACs (Perchyonok et al 2014). Several inclusion complexes with CDs have been reported in the promising field of environmental friendly pesticides (Benfeito et al 2013;Gao et al 2019b;Geng et al 2018;Kim et al 2019;Villaverde 2007;Villaverde et al 2004Villaverde et al , 2005Yanez et al 2012).…”
Section: Introductionmentioning
confidence: 99%